2021
DOI: 10.1080/21645515.2021.1969849
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of global vaccine certificate solutions for COVID-19

Abstract: Globally, measures, such as lockdown, quarantining, and physical distancing, have been implemented to curb the spread of COVID-19. As the vaccines are now available and reintegration into society is beginning, measures such as vaccine certificates are being implemented around the world. We conducted a scoping review to identify the initial digital solutions for COVID-19 vaccine certificates and evaluate them on the basis of purpose and use case, technological architecture, and ethical and legal implications. A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 16 publications
0
23
0
1
Order By: Relevance
“…Previous studies mostly focus on the necessity and possible issues to consider in COVID passes or vaccination certificates, or the perceptions of vaccine certificates among the general public [ 12 , 13 , 14 ]. As Mithani et al’s [15] preliminary study found out, most online articles on COVID-19 vaccine certificates centred around six themes, i.e., legality, technology, ethics, travel, policy and science. Most studies in the field of vaccination certificates have dealt with the functions and mechanisms of vaccination certificates in different countries/regions [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies mostly focus on the necessity and possible issues to consider in COVID passes or vaccination certificates, or the perceptions of vaccine certificates among the general public [ 12 , 13 , 14 ]. As Mithani et al’s [15] preliminary study found out, most online articles on COVID-19 vaccine certificates centred around six themes, i.e., legality, technology, ethics, travel, policy and science. Most studies in the field of vaccination certificates have dealt with the functions and mechanisms of vaccination certificates in different countries/regions [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of vaccine passports will not only boost the travel industry (Shaikh et al, 2021), but will also encourage more people to get vaccinated (Guidi et al, 2021). Vaccine passports will be widely used in the travel industry and other large gatherings such as sporting events, experts say (Walker, 2021;Mithani et al, 2022). China had achieved immunization of 86.73% of the population by 12May 2022 (Our World in Data, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many studies on the use of vaccine passports in the tourism industry, studies on consumers' awareness of vaccine passports are lacking (Shin et al, 2021;Mithani et al, 2022). Thus, this study extracted people's perception of vaccine passports/certificates into four factors.…”
Section: Introductionmentioning
confidence: 99%
“…First, acceptance of the EU Covid-19 certificate had been rarely studied before, especially among young people. Prior manuscripts have been limited to argue the ethical, legal, and policy validity of the EU Covid certificate [27,33,34]. In our study, we explored the opinions about the application of this certificate through a field investigation and found that it played a key role in factual vaccine uptake among students.…”
Section: Discussionmentioning
confidence: 94%